Interactive Soundscape Mapping for 18th-Century Naples: A Historically Informed Approach - Hasan Baran Firat; Massimiliano Masullo; Luigi Maffei (Acoustics, 2025)
This paper explores the application of a specialized end-to-end framework, crafted to study historical soundscapes, with a specific focus on 18th-century Naples. The framework combines historical research, natural language processing, architectural acoustics, and virtual acoustic modelling to achieve historically accurate and physically based soundscape reconstructions. Central to this study is the development of a Historically Informed Soundscape (HIS) map, which concentrates on the urban spaces of Largo di Palazzo and Via Toledo in Naples. Using virtual and audio-augmented reality, the HIS map provides 3D spatialized audio, offering an immersive experience of the acoustic environment of 18th-century Naples. This interdisciplinary approach not only contributes to the field of sound studies but also represents a significant methodological innovation in the analysis and interpretation of historical urban soundscapes. By incorporating historical maps as interactive graphical user interfaces, the project fosters a dynamic, multisensory engagement with the past, offering a valuable tool for scholars, educators, and the public to explore and understand historical sensory environments.